Identification and quantitative evaluation of nitrogen-converting organisms in a full-scale leachate treatment plant - MERTOĞLU, BÜLENT; BAKIRCI, KOZET (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2011)
The presence of ammonia nitrogen in landfill leachates poses a significant problem for treatment plant operators. The nitrification-denitrification process mostly carries out the nitrogen conversion in biological treatment systems. However, recent research shows that other processes by anaerobic ammonia-oxidizing bacteria (Anammox) and ammonia-oxidizing archaea (AOA) were also responsible for the removal of nitrogen in biological systems. In this study, the nitrogen-converting microorganisms in the Bursa Hamitler Leachate Treatment Plant were identified and monitored by using molecular tools. Fluorescent in situ hybridization (FISH) and slot-blot hybridization results showed that the Nitrosomonas and Nitrospira species were the dominant ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB), respectively. Quantitative real-time PCR results indicated that AOB, NOB, AOA and Anammox bacteria exist in the leachate treatment plant. However, the removal of ammonia can be ascribed mainly to nitrification because AOB (1.5%) and NOB (11.3%) were predominant among all nitrogen-converting bacteria. The results of the phylogenetic analysis based on amoA and 16S rDNA gene revealed that the uncultured bacterium clone 4-24, Kuenenia stuttgartiensis genome fragment KUST_E and the uncultured Crenarchaeota clone NJYPZT-C1 belong to AOB, Anammox and AOA populations, respectively, and were the dominant species in their cluster. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Ammonia; and nitrite-oxidizing bacteria; Ammonia-oxidizing archaea; Anammox; ANAEROBIC AMMONIUM OXIDATION; WATER TREATMENT PLANTS; REAL-TIME PCR; GRADIENT GEL-ELECTROPHORESIS; 16S RIBOSOMAL-RNA; LANDFILL LEACHATE; OXIDIZING ARCHAEA; ACTIVATED-SLUDGE; MICROBIAL-POPULATIONS; NITRIFYING BACTERIA